PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN LINGKUNGAN KERJA SEBAGAI VARIABEL MODERATING PADA DINAS LINGKUNGAN HIDUP SITUBONDO - Yudha Aji Ramadhan; Mohammad Yahya Arief; Riska Ayu Pramesthi (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of this study was to determine the influence of leadership and motivation on employee performance with the work environment as a moderating variable among employees at the Situbondo Environmental Service. The sampling technique used in this study was total sampling, with a saturated sample size of 40 employees. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Squares (PLS-SEM). The results showed that leadership had a negative but significant effect on employee performance, motivation had a positive and significant effect on employee performance, and the work environment did not moderate the influence of leadership on employee performance. The work environment significantly moderated the influence of motivation on employee performance.